Peran Indonesia dalam Upaya Penyelesaian Konflik antara Pemerintah Filipina dan Moro Nationalism Liberation Front (MNLF) - Hardi Alunaza SD; Dewa Anggara (Universitas Diponegoro, 2018)
The Moro Nationalism Liberation Front (MNLF) has long been perceived by the Philippine government as a threat. The continuity of this conflict resulted in the instability of the Philippine state which also affects its relations with other countries. Indonesia as a neighboring country and one region with the Philippines helped to resolve the conflict between the Philippine government and MNLF. The presence of Indonesia became a history of Indonesian diplomacy for the world peace struggle contained in Indonesia’s Preamble of the 1945 Constitution. This paper is attempts to answer that question using conflict theory from Max Weber which focuses on interaction in conflict resolution. The results of this paper indicates that Indonesian’s role in mediating the conflict resolution process resulted in a Final Peace Agreement which is the final peace agreement between the Philippine Government and MNLF.Keywords: Moro Nationalism Liberation Front (MNLF), Philippine, Indonesia, conflict resolution, Final Peace Agreement, mediation